2014
DOI: 10.1586/14760584.2015.964212
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine hesitancy, vaccine refusal and the anti-vaccine movement: influence, impact and implications

Abstract: Despite being recognized as one of the most successful public health measures, vaccination is perceived as unsafe and unnecessary by a growing number of parents. Anti-vaccination movements have been implicated in lowered vaccine acceptance rates and in the increase in vaccine-preventable disease outbreaks and epidemics. In this review, we will look at determinants of parental decision-making about vaccination and provide an overview of the history of anti-vaccination movements and its clinical impact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
609
1
27

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 762 publications
(706 citation statements)
references
References 163 publications
12
609
1
27
Order By: Relevance
“…Trust arises as an issue in numerous studies of why people do and do not vaccinate their children (Mills et al 2005;Dube, Vivion, and MacDonald 2015;Yaqub et al 2014), but the extent to which trust and distrust-as distinct concepts-shape vaccination decisions remains underexplored. In this study, we theoretically analyse trust and distrust to investigate parents' perceptions of the expert systems central to vaccination policy and practice in Australia, where approximately 3.3 per cent of children are not up to date with their vaccinations due to their parent or caregiver's active rejection of some or all vaccines (Beard et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trust arises as an issue in numerous studies of why people do and do not vaccinate their children (Mills et al 2005;Dube, Vivion, and MacDonald 2015;Yaqub et al 2014), but the extent to which trust and distrust-as distinct concepts-shape vaccination decisions remains underexplored. In this study, we theoretically analyse trust and distrust to investigate parents' perceptions of the expert systems central to vaccination policy and practice in Australia, where approximately 3.3 per cent of children are not up to date with their vaccinations due to their parent or caregiver's active rejection of some or all vaccines (Beard et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Current literatures consistently link institutional distrust in government, pharmaceutical companies, healthcare professions, and medical science and technology to vaccine rejection (Dube, Vivion, and MacDonald 2015). In a British study, parents of under-vaccinated children found it difficult to know where to place their trust and did not trust the government (Austin et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…A prime example of this phenomenon is the current antivaccination movement. With roots that trace back to a (now-discredited) 1998 study (Wakefield et al, 1998) linking the measles, mumps, and rubella vaccine to onset of autism in children, the modern-day antivaccine movement in the United States has been slowly growing (Dube, Vivion, and MacDonald, 2015). Beyond vaccination, scientific consensus has emerged on many other topics on which public skepticism endures in pockets, such as the safety of genetically modified food and the causes and consequences of climate change.…”
Section: In Its Ideal Form Community Citizen Science Is a Field In Wmentioning
confidence: 99%
“…This approach might not always work, however. As the ongoing challenge of parents who refuse to vaccinate their children attests, some people might be immune to this form of rational argument [15,16]. Moreover, the increasing availability and accessibility of unfiltered and unvetted information obtained from sources on the internet-including websites, blogs, social media networks, and the like-can radically affect the ability of physicians to counter preformed and deeply held beliefs with more reliable and trustworthy data [17][18][19].…”
Section: Making Decisions For Childrenmentioning
confidence: 99%